Association between triglyceride-glucose index and cataract among outpatient US adults - Qi Jin; Jin Huang; Liyun Gao; Jianmin Zhu (Frontiers in Medicine)
BackgroundAlthough numerous studies have associated a higher TyG index with various diseases, there is limited research on its potential link to cataract. This study seeks to investigate the relationship between the TyG index and cataract in the outpatient adult population in the United States.MethodsOur study used NHANES data from the 1999–2008 cycles. We applied weighted multivariate logistic regression to investigate the relationship between the TyG index and cataract in the United States and conducted subgroup analysis to assess the robustness of these associations across different populations.ResultsAmong 5,433 adults [2,699 (46.8%) male; 2,734 (53.2%) female], 1,038 (15.4%) had cataract. A fully adjusted model (i.e., model 2) showed that the highest quartile array of TyG index (Quartile IV) was positively associated with a higher risk of cataract among men (OR = 1.63 (1.10–2.43), p = 0.016). No difference was found in the female population.ConclusionOur research reveals that the highest quartile array of TyG index (Quartile IV) is associated with a higher risk of cataract among men. This suggests that elevated levels of this index may contribute to the likelihood of developing cataracts, emphasizing the need to consider this metabolic parameter when assessing eye health in male participants.